Cognition in spiders: Small brains on eight legs gain traction - Nelson, X. J. (Journal of zoology (1987), 2025)
Largely due to the work of arachnologist Robert Jackson, spiders are now considered as excellent animals in which to investigate sensory detection, perceptual processes and cognition—topics which are reviewed here. Spider sensory systems include, among others, mechanoreception of touch, substrate and airborne vibrations, as well as chemoreception (taste and smell) and, in some groups, exceptional vision. Some of these sensory systems are believed to be the most acute of any animal. This is mirrored in spider behaviour, which includes complex communication and signalling behaviour and eavesdropping to improve outcomes of future behaviour. Spiders also exhibit learning and reversal learning, significant problem‐solving ability, basic numerical ability, and possibly the ability to ‘plan’ ahead. I discuss the implications of having a small brain on the trade‐offs made by spiders regarding behavioural decisions, as well as evolutionary trade‐offs with respect to their ecology and even their morphology. Spiders make for particularly interesting study organisms due to the diversity of habitats in which they live and their foraging ecology. Some spiders are active cursorial hunters while others are sit‐and‐wait predators, and this has significant ramifications on the problems that they must overcome and on the sensory systems that they employ. Spiders also display extreme size differences between species and have the largest sexual size dimorphism (with females typically being larger) of any terrestrial animal. Furthermore, upon emerging from the eggsac, the fully formed spiderlings must hunt and behave as adults do, but may be orders of magnitude smaller. These attributes make spiders an appropriate group for studies of comparative cognition and to ascertain trade‐offs in cognition or behavioural flexibility due to miniaturization. This century will surely see an increase in spider cognition studies and a concomitant increase in the awareness of the sensory and cognitive abilities of these fascinating animals. Spiders are excellent subjects for studying sensory detection, cognition, and perception ‐ the central topics of this 2025 Thomas Henry Huxley Review by Prof. Ximena Nelson, based at the University of Canterbury in New Zealand. Their complex behaviours, advanced sensory systems (including chemoreception, vibrations, and vision), and problem‐solving abilities make spiders tractable subjects for understanding learning, communication, and even planning. With remarkable diversity, from size to hunting styles, spiders offer unique insights into how ecology shapes trade‐offs in animals with small brains. Expect more research on spider cognition in the coming years! Photo credit: Marshall Patrick.